Repeated social defeat-induced neuroinflammation, anxiety-like behavior and resistance to fear extinction were attenuated by the cannabinoid receptor agonist WIN55,212-2 - Lisboa, Sabrina Francesca (Neuropsychopharmacology, 2018)
Psychosocial stress contributes to the development of psychiatric disorders. Repeated social defeat (RSD) is a murine stressor that causes a release of inflammatory monocytes into circulation. Moreover, RSD-induced anxiety-like behavior is dependent on the recruitment of these monocytes to the brain. Activation of the endocannabinoid (ECB) system may modulate both neuroendocrine and inflammatory responses mediated by stress. Therefore, we hypothesized that a cannabinoid receptor agonist would attenuate RSD-induced inflammation, anxiety, and stress sensitization. To test this hypothesis, mice received an injection of the synthetic cannabinoid(1/2) receptor agonist, WIN55,212-2 (WIN; 1 mg/kg, intraperitoneally) daily for six consecutive days, 30 min before each exposure to RSD. Anxiety-like behavior, immune activation, neuroinflammation, and microglial reactivity were determined 14 h after RSD. RSD-induced anxiety-like behavior in the open field and in the EPM was reversed by WIN55,212-2. Moreover, WIN55,212-2 reduced the accumulation of inflammatory monocytes in circulation and brain after RSD and attenuated RSD-induced interleukin-1β (IL-1β) messenger RNA (mRNA) expression in microglia/macrophages. Increased ex vivo reactivity of microglia/monocytes to lipopolysaccharides (LPS) after RSD was also attenuated by WIN55,212-2. Next, fear expression, extinction, and recall were evaluated 24 and 48 h, respectively, after contextual fear conditioning, which took place 7 days after RSD. Here, RSD caused prolonged fear expression and impaired fear extinction recall, which was associated with increased IL-1β mRNA in the brain. Moreover, these stress-induced effects were reversed by WIN55,212-2. In conclusion, activation of cannabinoid receptors limited the immune and neuroinflammatory responses to RSD and reversed the short-term and long-term behavioral deficits associated with RSD.